Corruption as a stubborn retention of political power - Mora Ramirez, Rafael F. (2024)
The objective of this paper is to redefine the concept of political corruption by affirming that it mainly involves the idea of degradation of the concept of authority and implies the violation of established moral limits. This work is based on the qualitative approach; therefore, we have resorted to the reading and consultation of relevant and specialized sources in political philosophy. In this sense, taking philosophy as a basis and with the purpose of constructing solid arguments, the analysis of such information will be carried out. As a result, it has been suggested that the need for good education and knowledge of legal aspects should be emphasized so that the population can oppose the bad ruler. It is concluded that a corrupt government is one that opposes democracy, totalizes power, assumes authoritarianism as doctrine and does not respect citizens.